IFPRI Malawi maize market report, August 2025 - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
Highlights Retail prices of maize increased on average by 16 percent in August. Prices rose in all monitored markets across all regions of Malawi despite continued imports. Depreciation of the Malawi kwacha (at market rates) against its Zambian and Mozambican counterparts dampened the mitigating effects of imports on maize price increases.